BLOCKCHAIN, BIG DATA AND MACHINE LEARNING: TRENDS AND APPLICATIONS - Kumar, Neeraj (Computer scientist), editor.; Gayathri, N.; Md. Arafatur Rahman; Balamurugan, B. (Boca Raton, FL : CRC Press, 2020)
Includes bibliographical and references